The improvement design of two-colour pyrometry for pulsed laser deposition system. Issue 1 (1st May 2022) - Liang, T.; Ningsih, K.; Mackenzie, J. I.; Prentice, J.; Yasin, M.
Abstract: In this work, we develop a digital pyrometry with an automatic control system. A two-colour pyrometer is applied to measure the substrate surface temperature in the pulsed laser dep-osition (PLD) system. A digital computer and two-colour photodetector are coupled to obtain the substrate surface temperature and the output signal from the respective detectors with high accuracy. These sets enable us to determine the substrate temperature during the process of deposition remotely and potentially allow us to develop control routines for maintaining a constant temperature throughout the process. The designed system has a broad spectral response range from 0.32 to 1.7μm and achieves a deficient full-scale temperature error of <1.8°C. Factors affecting the temperature measurements are studied to identify the sensor limitations, such as possible damage on the two-colour photodetectors, spectral losses, responsivity, and the distance between the photodetector end to the substrate. Finally, this pyrometric system is applied in the PLD process to maintain a stable substrate surface temperature.